Students’ Challenges in Writing Paragraph at Sar-e-Pul Higher Education Institute - Haidari, Sultan Ali; Zada, Mohammad Zamin (Journal of Natural Language and Linguistics, 2025)
The current study aimed to discover EFL undergraduate students’ major writing paragraph challenges. The data was collected through questionnaire and 28 third-year students of English Language and Literature Department of Sar-e-Pul Higher Education Institute participated in this study. The data was analyzed quantitatively by using SPSS software program. The results of this study showed that students had several challenges in writing paragraph although they followed the stages of writing; they had positive attitudes and were eager to practice writing. They did not know the organization and functions of parts of paragraph and they had difficulties on how to give details and support the main idea of the paragraph. Also the results showed that the lack of vocabulary is the reason for writing poor paragraph. In addition, organization, coherence, cohesion, spelling, and grammar are the major challenging aspects in writing paragraph. Therefore, EFL teachers are recommended to utilize active learning methods, assign students writing different paragraphs, and give feedback in order to avoid students’ challenges.